IMPLENTASI AJARAN SUSILA DALAM NGUSABA KAJA DI DESA ADAT BUGBUG KARANGASEM - Ni Putu Gatriyani; I Wayan Sudiarta (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
Ngusaba Kaja is the embodiment of an aesthetic experience when the state of the soul is experiencing peace and purity. This ascent can only be achieved by immanent appreciation and practice of the teachings of Hinduism. Ngusaba Kaja grows, lives and develops as a religious culture. The study in this study, focused on the implementation of the ethical teachings contained in the Ngusaba Kaja, so that they can be understood and practiced in people's lives. This study of Ngusaba Kaja uses several theories, namely; the theory of Structural Functionalism, and the theory of religion as an auxiliary theory which is supported by literature studies and through information from resource persons as informants. Ngusaba Kaja as part of culture, is a symbol of society and contains values that live in society.The existence of Ngusaba Kaja can be understood through the functions and meanings contained in it. Its existence needs to be explored, developed and preserved. One conservation step, even on the simplest scale, would have a defensive meaning, in alerting the totality of oneself to face the wave of pluralism in the next century.Keywords: Teachings of Susila and Ngusaba Kaja